(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2025)
Cybercrime in Malaysia has become increasingly alarming, with various cases involving hacking, online fraud, malware attacks, and data breaches. Although there are more than 30 laws related to cyber activities, the enforcement of these laws remains ineffective in addressing increasingly complex threats. This study employs qualitative data analysis to examine the issues and challenges in combating cybercrime in Malaysia. Key challenges identified include the rapid advancement of technology, the evolving definition of cybercrime, jurisdictional challenges in cross-border investigations, and inadequate digital evidence. Additionally, difficulties in pinpointing the exact location of cybercriminals and issues related to the preservation of digital data pose significant obstacles to effective investigation and prosecution. This study proposes improvements to existing cyber laws, including amendments to the Communications and Multimedia Act 1998, the Computer Crimes Act 1997, and the Personal Data Protection Act 2010, to enhance the enforcement and investigation of cybercrimes. With more dynamic approaches, these laws can become more responsive in reducing the risks posed by the rapidly evolving cyber threats. Keywords: Cybercrime, cybercrime definition, cross-border investigation, digital forensics, legal framework, digital security Full Text: PDF